USM TO ESTABLISH HIGHER EDUCATION HUB IN THE AFRICAN CONTINENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 27 April 2016 – Universiti Sains Malaysia (USM) has been offered the opportunity to establish a hub for higher education to provide for postgraduate degree programmes at the Master’s and Ph.D levels, especially in the fields of Management and Business Management, through a cooperation with Makerere University Business School (MUBS) Kampala, Uganda.